Novelties in Cuphea (Lythraceae) from Serra do Espinhaço and Serra da Mantiqueira, and a key to the species from Minas Gerais state, Brazil - Facco, Marlon Garlet; Cavalcanti, Taciana Barbosa (Phytotaxa, 2022)
Throughout the taxonomic studies towards the global revision of the genus Cuphea, two new species endemic to the state of Minas Gerais, Brazil, and classified in C. sect. Euandra subsect. Hilariella, were identified: C. dryadica from the Serra da Mantiqueira complex, in the Atlantic Rainforest, and C. venosa from the Septentrional block of the Serra do Espinhaço, in the Cerrado biome. Both species are described, illustrated, commented on their ecological aspects and taxonomic affinities. According to a preliminary assessment of the conservation status, the new species were categorized as Critically Endangered. An identification key for the 52 species of Cuphea that occur in the state of Minas Gerais is given.